Isotopic composition on ground ice in Western Yamal (Marre-Sale) - I. D. Streletskaya; A. A. Vasiliev; G. E. Oblogov; A. G. Matyukhin (Лëд и снег, 2015)
The profile of Quaternary sediments near Marre-Salle polar station, Western Yamal Peninsula, has large bodies of tabular ground ice. This profile is considered strata-typical and critical in understanding of paleogeographic conditions of the Arctic in Pleistocene-Holocene. However, interpretation of the profile is under discussion. It consists of two distinct strata: upper layer of 10–15 m thick represented by continental sediments and lower one with a thickness of more than 100 m represented by marine sediments. Lower layer of saline marine clays has lenses of tabular ground ice (more than 20 m thick), the bases of which are below the sea level. Upper continental layer is characterized by syngenetic ice-wedges of different generations. Samples were collected from ice-wedges and tabular ground ice for chemical and isotope analysis. The results of the analysis allow to reconstruct paleogeographic conditions of the sedimentation and freezing of Quaternary sediments. Heavy stable isotope content and relationship between oxygen and hydrogen isotopes show that the ice bodies in the lower layer were formed in-situ within the ground. In the upper layer, heavier isotope content found in younger ice-wedges relative to the old-generation wedges. Formation of massive syngenetic Upper-Pleistocene ice-wedges occurred in conditions of colder winter temperatures than at present. Syngenetic Holocene wedges were formed after Holocene Optimum under winter conditions similar to present. Younger ice wedges formed smaller polygons, were smaller and often were developing in the locations of the degraded old wedges. Results of the isotope analysis of various types of ground ice near Marre-Sale allow reconstructing changes of marine sedimentation to continental one around Kargino time (MIS 3) and changes in climatic conditions in Arctic in Late Pleistocene and Holocene.